2y-5x-10=0

Simple and best practice solution for 2y-5x-10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-5x-10=0 equation:


Simplifying
2y + -5x + -10 = 0

Reorder the terms:
-10 + -5x + 2y = 0

Solving
-10 + -5x + 2y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + -5x + 10 + 2y = 0 + 10

Reorder the terms:
-10 + 10 + -5x + 2y = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -5x + 2y = 0 + 10
-5x + 2y = 0 + 10

Combine like terms: 0 + 10 = 10
-5x + 2y = 10

Add '-2y' to each side of the equation.
-5x + 2y + -2y = 10 + -2y

Combine like terms: 2y + -2y = 0
-5x + 0 = 10 + -2y
-5x = 10 + -2y

Divide each side by '-5'.
x = -2 + 0.4y

Simplifying
x = -2 + 0.4y

See similar equations:

| 6.5/3x+5=6 | | 6n-32=n^2-6n+3 | | U+2.87=6.56 | | 7(x-1)=12 | | 3n-32=n^2-6n+3 | | m+4+8m=-23 | | 16+n=30 | | -(a-4)=1 | | -y^2+4y-1=0 | | 8(4r+5+9s)= | | -8y+5=-6 | | 4-9X=3-10X-(7-X) | | 4(a-3)+a=15+2a+9 | | 3y+8=65 | | Y=-7lnx | | 2x-7=6x+3 | | 2(-3-1)+(2y+7)= | | 1/3(9x+3/4)-5=2/3(12x+6) | | 4x-14=-1 | | 8y=-4x+42 | | 98x^2=72 | | f(x)=4x^2+15 | | x^3=7x-2 | | .4w^10+9m^2=0 | | 1/2(8x-1/5)-3x=2/6x | | 12(2)-8y=12 | | p=n(120-n)-50n | | 2x^2-2=-10 | | 6+17=5x-4 | | 9x^2=15x^2-10x | | -7-5h=-127 | | 0=6x^2-10x |

Equations solver categories